Better speech-in-noise comprehension is associated with enhanced neural speech tracking in older adults with hearing impairment. (June 2022) - Schmitt, Raffael; Meyer, Martin; Giroud, Nathalie
Abstract: The alignment between low-frequency activity in the brain and slow acoustic modulations in the speech signal depicts a core principle in present theories of speech perception—a process referred to as 'neural speech tracking'. While most older adults, particularly those with highly prevalent age-related hearing loss, have difficulties with speech perception and comprehension, the impact of hearing loss on neural speech tracking is still unclear. In this study we investigated the effects of pure-tone hearing loss and different types of background noise on the neural tracking response in a large sample of older adults ( N = 101). Furthermore, we examined whether the neural tracking response was predictive for speech comprehension. For this purpose, we obtained scalp EEG from our participants who had varying degrees of pure-tone hearing loss (7.5–59.6 dB HL for .5–8 kHz pure tones) while they listened to sentences in quiet, pink and multi-talker babble noise. Speech tracking was quantified by computing the cross-correlation between the EEG signal and the amplitude envelope of the sentences heard. A higher degree of pure-tone hearing loss was associated with greater neural speech tracking (i.e., greater cross-correlation). Additionally, neural speech tracking showed a positive association with speech comprehension. This relationship was modulated by the degree of pure-tone hearing loss with hearing-impaired participants benefitting more from greater neural speech tracking. Our results highlight the potential of neural speech tracking as an objective measure of speech comprehension and as a possible target mechanism for clinical interventions such as neurofeedback. Furthermore, the interaction between speech tracking and pure-tone hearing loss suggests a compensatory mechanism by which the hearing-impaired rely more on slow amplitude modulations in the speech signal.